Efforts to Improve Learning Outcomes with Reward Techniques in Integrative Thematic Learning for Grade I Students of SDN 1 Sawangan, Patikraja District - Saputri, Sulih Ristyani Ayu (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve learning outcomes with reward techniques in integrative thematic learning for grade I SDN 1 Sawangan students. The research carried out was Classroom Action Research (PTK) which was carried out through 3 learning cycles which were preceded by an initial cycle or pre-cycle. Learning steps taken as action or corrective measures include cycle I, cycle II and cycle III to determine the development of students. Each cycle includes planning, implementing actions, observing, and reflecting. In cycle I, students who completed the postest were 28.57%. In cycle II, students who completed the postest were 57.14%. In cycle III, students who completed the postest were 85.71%. These results indicate that the reward technique can improve student learning outcomes, especially in learning the theme of my family, the sub-theme of class I family members at SDN 1 Sawangan, Patikraja District.